CONCEPTUAL STUDY OF DUSHI VISHA WITH SPECIAL REFERENCE TO INANIMATE, ANIMATE & ARTIFICIAL POISONS - Gatfane Rupali; Denge Kalpana (International Journal of Applied Ayurved Research, 2017)
Dushi Visha is one of the unique concept explained in Ayurveda. It is a type of toxin which remains inside the body for long & then produces various ill effects on the body. In present era, people are exposing to various toxins in day to day life which is causing various health problems. There are many such illnesses where treatment does not work, as it is not eliminating the root cause. The ancient concept of dushi visha seems to be more relevant in this context. So this topic is selected to study the concept comprehensively with the object of highlighting it with modern approach.